Development and Validation of Instruments to Measure the Competence of Road Engineering Experts - Heru Budi Utomo, Slamet Prawiro Harto, Amat Jaedun (International Journal of Advanced Science and Technology, 2020)
This research aims to produce a comprehensive assessment instrument that measures the competence of road and bridge engineering experts. This type of research is research and development using Borg and Gall model modifications, into five phases, (1) collecting information; (2) Making planning; (3) Prepare the product form; (4) Validate the expert (5) Implement product revisions. The competency assessment instrument of road and bridge engineering is a written test instrument and consists of 37 items. Test the validity of the instrument content using the formula Aiken and judged by 12 experts. Data analysis techniques use descriptive statistics to test product readability. This research generates a valuation instrument with a valid category according to the expert and has good readability, so it can be used as an alternative instrument in assessing the competence of road engineering experts in students.